Marine conservation from a First Nations' perspective : a case study of the principles of the Hul'qumi'num of Vancouver Island, British Columbia - Ayers, Cheri Anne. (2005)
Evidence for the decline of marine biodiversity is being noted worldwide (Pauly and Watson, 2003). Indigenous peoples around the world have a key role to play in marine conservation efforts. With the collapse of many fisheries stocks, including stocks in the Georgia Strait of British Columbia, Canada, the Canadian Federal Government is pursuing conservation strategies such as Marine Protected Areas (MPAs). Section 35 of Canada's Constitution Act protects indigenous peoples' rights, such as the right to harvest natural resources for food, social and ceremonial use. Conservation efforts that potentially infringe upon Aboriginal rights secure a duty to consult and accommodate First Nations' interests on the Government of Canada. Indigenous peoples on Canada's West Coast ofen oppose the creation of MPAs as these have the potential to impact their indigenous rights. This opposition has contributed to the delay in the development of MPAs on the Pacific Coast of Canada. This research contributes to understanding of indigenous use of marine resources and how effective government proposed MPAs are in meeting the conservation goals and perspectives of the Hul'qumi'num peoples. First Nations' marine conservation and management principles, goals and objectives are explored, through a case study of a Central Coast Salish indigenous group, the Hul'qumi'num. These approaches are compared to current government principles and strategies. Some similarities exist between the two, although there are fundamental differences that may be dificult to reconcile. The Hul'qumi'num worldview that everything is connected has some similarities to ecosystem-based management where humans are viewed as part of the ecosystem. However, in a Hul'qumi'num philosophy, humans are a fundamental component of the ecosystem, whereas ecosystem-based management recognizes humans as part of the ecosystem in order to better manage anthropogenic impacts. Simply integrating traditional ecological knowledge in current management efforts does not go far enough ...